Pemanfaatan Limbah Abu Terbang (Fly Ash) Batubara Sebagai Bahan Pembuatan Beton Geopolimer - Yuanda, Dedi; Fadli, Ahmad; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fly ash has a high content of silica and alumina that potential as a subtitute of portland cement. In this study fly ash is utilized for making geopolimer concrete materials. The geopolymer was sinthesized from fly ash Paiton Power Plant using 8 ,10, 12 and 14 NaOH solution and Na-silicate/NaOH. Na-silicate/NaOH ratio used in this study were 0,8;1,2;1,6;2,0. and 80oC for curing temperature. The geopolymer were test in porosity, compressive strength, leached value and it’s morphology. The compressive strength test showed that 14 NaOH solution and 2.0 Na-silicate/NaOH weight ratio were the strongest. It’s value was 7.56 MPa and it’s porosity was 0,0249. It was also found that the compressive strength increases with the composition of NaOH solution and Na-silicate/NaOH weight ratio. The result of TCLP test shows that for Pb, Cu, Cr are still below the quality standards based on PP No.85 TH 1999 and is still considered harmless.Keywords: geopolymer concrete;fly ash; NaOH solution; leached